Making Powder of Temulawak Rhizome (Cucum Axanthoriza) to Increase the Application - Aisyah Mentari; Ayus Diningsih (Journal of Public Health and Pharmacy)
Background: Temulawak (Curcuma xanthorrhiza), has traditionally been widely used for medicinal purposes or as a drink to maintain health.